Incorporating Weight Management and Physical Activity Throughout the Cancer Care Continuum: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The National Cancer Policy Forum of the National Academies of Sciences, Engineering, and Medicine held a public workshop, Incorporating Weight Management and Physical Activity Throughout the Cancer Care Continuum, on February 13 and 14, 2017, in Washington, DC. The purpose of this workshop was to highlight the current evidence base, gaps in knowledge, and research needs on the associations among obesity, physical activity, weight management, and health outcomes for cancer survivors, as well as to examine the effectiveness of interventions for promoting physical activity and weight management among people living with or beyond cancer. Workshop sessions also reviewed the opportunities and challenges for providing weight management and physical activity interventions to cancer survivors. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

The Drug Development Paradigm in Oncology: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Advances in cancer research have led to an improved understanding of the molecular mechanisms underpinning the development of cancer and how the immune system responds to cancer. This influx of research has led to an increasing number and variety of therapies in the drug development pipeline, including targeted therapies and associated biomarker tests that can select which patients are most likely to respond, and immunotherapies that harness the body’s immune system to destroy cancer cells. Compared with standard chemotherapies, these new cancer therapies may demonstrate evidence of benefit and clearer distinctions between efficacy and toxicity at an earlier stage of development. However, there is a concern that the traditional processes for cancer drug development, evaluation, and regulatory approval could impede or delay the use of these promising cancer treatments in clinical practice. This has led to a number of efforts—by patient advocates, the pharmaceutical industry, and the Food and Drug Administration (FDA)—to accelerate the review of promising new cancer therapies, especially for cancers that currently lack effective treatments. However, generating the necessary data to confirm safety and efficacy during expedited drug development programs can present a unique set of challenges and opportunities.
Keywords: Health and Medicine

Making Medicines Affordable: A National Imperative - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Thanks to remarkable advances in modern health care attributable to science, engineering, and medicine, it is now possible to cure or manage illnesses that were long deemed untreatable. At the same time, however, the United States is facing the vexing challenge of a seemingly uncontrolled rise in the cost of health care. Total medical expenditures are rapidly approaching 20 percent of the gross domestic product and are crowding out other priorities of national importance. The use of increasingly expensive prescription drugs is a significant part of this problem, making the cost of biopharmaceuticals a serious national concern with broad political implications. Especially with the highly visible and very large price increases for prescription drugs that have occurred in recent years, finding a way to make prescription medicines—and health care at large—more affordable for everyone has become a socioeconomic imperative.
Keywords: Health and Medicine

Improving Cancer Diagnosis and Care: Patient Access to Oncologic Imaging and Pathology Expertise and Technologies: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Rapid advances in cancer research, the development of new and more sophisticated approaches to diagnostic testing, and the growth in targeted cancer therapies are transforming the landscape of cancer diagnosis and care. These innovations have contributed to improved outcomes for patients with cancer, but they have also increased the complexity involved in diagnosis and subsequent care decisions.
Keywords: Health and Medicine

Long-Term Survivorship Care After Cancer Treatment: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The 2006 Institute of Medicine (IOM) consensus study report From Cancer Patient to Cancer Survivor: Lost in Transition made recommendations to improve the quality of care that cancer survivors receive, in recognition that cancer survivors are at risk for significant physical, psychosocial, and financial repercussions from cancer and its treatment. Since then, efforts to recognize and address the unique needs of cancer survivors have increased, including an emphasis on improving the evidence base for cancer survivorship care and identifying best practices in the delivery of high-quality cancer survivorship care.
Keywords: Health and Medicine

Urbanization and Slums: Infectious Diseases in the Built Environment: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The urban built environment is a prime setting for microbial transmission, because just as cities serve as hubs for migration and international travel, components of the urban built environment serve as hubs that drive the transmission of infectious disease pathogens. The risk of infectious diseases for many people living in slums is further compounded by their poverty and their surrounding physical and social environment, which is often overcrowded, is prone to physical hazards, and lacks adequate or secure housing and basic infrastructure, including water, sanitation, or hygiene services.
Keywords: Health and Medicine

Biomarkers of Neuroinflammation: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Neuroinflammation is a burgeoning area of interest in academia and biopharma, with a broadly acknowledged role in many central nervous system (CNS) disorders. However, there is little agreement on the pathophysiological mechanisms that underlie the manifestations of neuroinflammation in the CNS compartment and how neuroinflammation operates as a driver and also as a consequence of disease in the brain. Moreover, another unclear area is how to translate increased understanding of the mechanisms that underlie neuroinflammation and its manifestations in the CNS to therapeutics.
Keywords: Health and Medicine

The Future of Health Services Research: Advancing Health Systems Research and Practice in the United States - National Academy of Medicine (The National Academies Press, 2018)
Health services research is "the multidisciplinary field of scientific investigation that studies how social factors, financing systems, organizational structures and processes, health technologies, and personal behaviors affect access to health care and the quality and cost of health care." Since the 1960s, health services research has provided the foundation for progress, effectiveness, and value in health care. Ironically, at a time in which appreciation has never been higher for both the need and potential from health services research, the political and financial support for sustenance and growth appear to be weakening. With funding support from AcademyHealth, the American Association of Colleges of Nursing, the American Board of Family Medicine, the American Society of Anesthesiologists, the Association of American Medical Colleges, the Federation of American Hospitals, and the Robert Wood Johnson Foundation, this National Academy of Medicine Special Publication identifies the range of issues that health services research must consider, address, and potentially overcome to transform the field to meet the needs of a 21st-century health care system. These issues are broad, multidisciplinary, and will require a coordinated effort to address—as well as dedicated and sustainable funding. Federal support for health services research has never been more critical. Now is a critical time for the field to articulate its priorities, demonstrate its utility, and transform to meet the needs of a 21st-century health care system. The physical and financial health of the nation is at stake.
Keywords: Health and Medicine

Aging and Disability: Beyond Stereotypes to Inclusion: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Many different groups of people are subject to stereotypes. Positive stereotypes (e.g., "older and wiser") may provide a benefit to the relevant groups. However, negative stereotypes of aging and of disability continue to persist and, in some cases, remain socially acceptable. Research has shown that when exposed to negative images of aging, older persons demonstrate poor physical and cognitive performance and function, while those who are exposed to positive images of aging (or who have positive self-perceptions of aging) demonstrate better performance and function. Furthermore, an individual's expectations about and perceptions of aging can predict future health outcomes. To better understand how stereotypes affect older adults and individuals with disabilities, the National Academies of Sciences, Engineering, and Medicine, with support from AARP, convened a public workshop on October 10, 2017. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Behavioral and Social Sciences

Exploring a Business Case for High-Value Continuing Professional Development: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Continuing education, continuing professional development, and high-value continuing professional development exist along a continuum. Continuing education (CE) often is associated with didactic learning methods, such as lectures and seminars, which take place in auditoriums and classrooms, and is often viewed by health professionals as merely a path to maintaining licensure and certification through the accumulation of credits. Continuing professional development (CPD), in contrast, embraces a wider array of learning formats and methods that are driven by learners.
Keywords: Health and Medicine

People Living with Disabilities: Health Equity, Health Disparities, and Health Literacy: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Poor health literacy has many negative consequences for achieving the quadruple aim of better care, improving the health of the community and the population, providing affordable care, and improving the work life of health care providers, and those consequences disproportionately affect those individuals with disabilities and those who experience health disparities. To better understand how health literacy, health equity, and health disparities intersect for individuals living with disabilities, the Roundtable on the Promotion of Health Equity and the Elimination of Health Disparities and the Roundtable on Health Literacy jointly sponsored a workshop that was held on June 14, 2016, in Washington, DC. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Health-Care Utilization as a Proxy in Disability Determination - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The Social Security Administration (SSA) administers two programs that provide benefits based on disability: the Social Security Disability Insurance (SSDI) program and the Supplemental Security Income (SSI) program. This report analyzes health care utilizations as they relate to impairment severity and SSA’s definition of disability. Health Care Utilization as a Proxy in Disability Determination identifies types of utilizations that might be good proxies for “listing-level” severity; that is, what represents an impairment, or combination of impairments, that are severe enough to prevent a person from doing any gainful activity, regardless of age, education, or work experience.
Keywords: Health and Medicine

Medication-Assisted Treatment for Opioid Use Disorder: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
On October 30 and 31, 2018, the National Academies of Sciences, Engineering, and Medicine held a 1.5-day workshop on Medication-Assisted Treatment (MAT) for Opioid Use Disorder (OUD). The workshop participants reviewed the current knowledge and gaps in understanding regarding the effectiveness of MAT for treating OUD, examined the available evidence on the range of parameters and circumstances in which MAT can be effectively delivered (e.g., duration of treatment, populations, settings, and interventions to address social determinants of health as a component of MAT), identified challenges in implementation and additional research needed. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Opportunities to Enhance the Health and Well-Being of the Department of Homeland Security Law Enforcement Workforce: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
On January 17 and 18, 2018, the National Academies of Sciences, Engineering, and Medicine hosted a workshop focused on enhancing the health and well-being of the Department of Homeland Security’s (DHS) law enforcement workforce. The workshop featured presentations in two main topic areas: (1) the operational stressors and environments faced by the DHS law enforcement workforce, and (2) strategies that can be used to address these stressors and promote overall health and well-being. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Review of NASA's Evidence Reports on Human Health Risks: 2017 Letter Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
This is the fifth, and final, in a series of letter reports that provide an independent review of the more than 30 evidence reports that NASA has compiled on human health risks for long-duration and exploration spaceflights. This letter report reviews five evidence reports and examines the quality of the evidence, analysis, and overall construction of each report; identifies existing gaps in report content; and provides suggestions for additional sources of expert input.
Keywords: Health and Medicine

Models and Strategies to Integrate Palliative Care Principles into Care for People with Serious Illness: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Palliative care is the interdisciplinary specialty focused on improving quality of life for people with serious illness and their families. This interdisciplinary care is provided by doctors, nurses, social workers, chaplains and others who work together with the patient's other doctors to provide an extra layer of support. Such care is appropriate for people at any age and at any stage in a serious illness, and can be provided together with curative treatment to address clinical, emotional, psychosocial and spiritual concerns of the patient and their family. To better understand how the principles of palliative care can be integrated into the overall provision of care and services to those facing serious illness, the Roundtable on Quality Care for People with Serious Illness held a public workshop in April 2017. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Understanding Disparities in Access to Genomic Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Genomic medicine is defined as the routine use of genomic information about an individual as part of his or her clinical care as well as the health outcomes and policy implications of that clinical use. It is one approach that has the potential to improve the quality of health care by allowing practitioners to tailor prevention, diagnostic, and treatment strategies to individual patients. In recent years, research breakthroughs, technological advances, and the decreasing cost of DNA sequencing have led to the wider adoption of genomic medicine. However, as with the introduction of new technologies into health care, there are concerns that genetic and genomic testing and services will not reach all segments of the population both now and in the near future, and there remains a gap in knowledge regarding potential health care disparities in genomic medicine and precision health approaches.
Keywords: Health and Medicine

Financing and Payment Strategies to Support High-Quality Care for People with Serious Illness: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Millions of people in the United States live with serious illnesses such as cancer, heart disease, chronic obstructive pulmonary disorder (COPD), amyotrophic lateral sclerosis, Parkinson’s disease, and dementia—often for many years. Those facing serious illness have a range of interconnected medical and non-medical needs, and the way their care is financed has a large impact on the care they receive. Medicare is the predominant payer, but both Medicaid and private payers also play significant roles in financing care for serious illness. In an effort to address the complex needs of people with serious illness, public and private health care payers are testing innovative financing strategies and alternative payment models. These innovative approaches signal a gradual transition from the traditional-fee-for-service system that pays providers based on the quantity of services to a system based on the value of care provided and a heightened focus on improved quality of care at lower cost.
Keywords: Health and Medicine

Considerations for the Design of a Systematic Review of Care Interventions for Individuals with Dementia and Their Caregivers: Letter Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Considerations for the Design of a Systematic Review of Care Interventions for Individuals with Dementia and Their Caregivers: Letter Report provides input into the design of an Agency for Healthcare Research and Quality (AHRQ) systematic review of evidence on effective care-related interventions for people with dementia and their caregivers. This letter report describes potential changes and considerations for the key questions and study design that would result in the most informative and timely evidence review on this topic.
Keywords: Health and Medicine

Understanding the Economics of Microbial Threats: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Microbial threats, including endemic and emerging infectious diseases and antimicrobial resistance, can cause not only substantial health consequences but also enormous disruption to economic activity worldwide. While scientific advances have undoubtedly strengthened our ability to respond to and mitigate the mortality of infectious disease threats, events over the past two decades have illustrated our continued vulnerability to economic consequences from these threats.
Keywords: Health and Medicine